Nutrition of young basketball players in training camp - Rubana, I. M.; Libaze, I. (LASE Journal of Sport Science, 2010)
The objective of the current study was to investigate the nutritional intake of young basketball players over a ten day period during training camp. For this purpose we have analyzed trainings to estimate daily energy expenditure. Questionnaire and interview were necessary for the evaluation of the daily menu. We proceeded with anthropometry and statistical analysis to obtain the results. The results showed that average daily amount of energy intake (kcal) for athletes was sufficient ranging from minimum to medium weight, but insufficient for the athlete with the largest weight. Average daily intake of protein 2.6g/kg (16.7%E) was consistent with the requirements for the young athletes, taking into account the age and increased physical load. Average daily intake of fat (30.02%) was slightly higher as desired at the expense of the high proportion of increased saturated fat. Average daily intake of carbohydrate was not enough: 7.2g/kg (52.9%E). The young athletes' diet during the training camp did not include sufficient amounts of fruit and vegetables, as well as a variety of products. In conclusion, average energy intake of young athletes during the training camp was sufficient for the athletes with minimum and medium weight, but insufficient for the athlete with the largest weight, therefore resulting in an energy deficit. Average protein intake was sufficient and corresponded to the upper limit of the daily requirement: 2.6 g/kg daily. The percentage of proteins provided on average 16.7% of the energy intake. Average daily fat intake (30.0% from the energy intake) was slightly increased at the expense of animal origin saturated fat. Taking into account the increased amount of physical work, the carbohydrate intake was insufficient (7.0 g/kg). Average daily carbohydrate consumption provided 52% of the energy intake which should be increased at the expense of fat. The menu provided for the young basketball players during the training camp only partially corresponded to the principle of variety.